2012
DOI: 10.1095/biolreprod.112.099960
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Bone Marrow-Derived Vascular Progenitor Cells in Neovascularization During Formation of the Corpus Luteum in Mice1

Abstract: Neovascularization is necessary for formation of the corpus luteum (CL) and includes angiogenesis and vasculogenesis. Vasculogenesis is the formation of new blood vessels by bone marrow-derived endothelial progenitor cells. Here we investigated whether vasculogenesis occurs in neovascularization during CL formation. Mice transplanted with bone marrow from transgenic mice expressing green fluorescent protein (GFP) were injected with equine chorionic gonadotropin and human chorionic gonadotropin (hCG) to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
1
17
1
Order By: Relevance
“…In this model, bone marrow-derived vascular progenitor cells are tracked by transplanting bone marrow cells from GFP-transgenic mice into the recipient mice whose immune systems were compromised by irradiation. The irradiation damages the ovaries [10], which makes it difficult to examine physiological development of follicles in the BMT model. In addition, when the mice are treated with gonadotropins, the damaged basement membrane of the preovulatory follicle allows vascular endothelial cells to enter the granulosa cell layer before ovulatory LH surge [10].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this model, bone marrow-derived vascular progenitor cells are tracked by transplanting bone marrow cells from GFP-transgenic mice into the recipient mice whose immune systems were compromised by irradiation. The irradiation damages the ovaries [10], which makes it difficult to examine physiological development of follicles in the BMT model. In addition, when the mice are treated with gonadotropins, the damaged basement membrane of the preovulatory follicle allows vascular endothelial cells to enter the granulosa cell layer before ovulatory LH surge [10].…”
Section: Methodsmentioning
confidence: 99%
“…The irradiation damages the ovaries [10], which makes it difficult to examine physiological development of follicles in the BMT model. In addition, when the mice are treated with gonadotropins, the damaged basement membrane of the preovulatory follicle allows vascular endothelial cells to enter the granulosa cell layer before ovulatory LH surge [10]. Furthermore, low dose irradiation is reported to stimulate vasculogenesis in various organs [16,17].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst, Turner et al (2011) recently demonstrated that macrophages play a crucial role in maintaining vascular integrity in mice. This concept is further supported by the observations that bone marrow-derived vascular progenitor cells and macrophages contribute to neovascularisation during CL formation (Kizuka et al 2012). The role of macrophages is potentially the most important since these cell can be differentiated into the 'tissue remodelling' M2 phenotype by the luteal microenvironment.…”
mentioning
confidence: 85%